World Economic Outlook, April 2019 : Growth Slowdown, Precarious Recovery. (World Economic Outlook; World Economic Outlook ;, 2019)
After strong growth in 2017 and early 2018, global economic activity slowed notably in the second half of last year, reflecting a confluence of factors affecting major economies. China's growth declined following a combination of needed regulatory tightening to rein in shadow banking and an increase in trade tensions with the United States. The euro area economy lost more momentum than expected as consumer and business confidence weakened and car production in Germany was disrupted by the introduction of new emission standards; investment dropped in Italy as sovereign spreads widened; and external demand, especially from emerging Asia, softened. Elsewhere, natural disasters hurt activity in Japan. Trade tensions increasingly took a toll on business confidence and, so, financial market sentiment worsened, with financial conditions tightening for vulnerable emerging markets in the spring of 2018 and then in advanced economies later in the year, weighing on global demand. Conditions have eased in 2019 as the US Federal Reserve signaled a more accommodative monetary policy stance and markets became more optimistic about a US-China trade deal, but they remain slightly more restrictive than in the fall.